ANALISIS KARAKTERISTIK IKLIM DAN HUJAN PADA LAHAN PERTANIAN DI KECAMATAN KEDIRI KABUPATEN LOMBOK BARAT - Pamungkas, Gilang Darma; Iemaaniah, Zuhdiyah Matienatul; Bustan, Bustan (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
The availability of water on Earth's surface is influenced by rainfall and climate in a particular region. Water is a basic necessity for human beings and is used for various daily life purposes. One of these purposes is irrigation in agricultural lands. The agricultural sector has traditionally relied on the availability of water from rainfall and the suitability of the climate. Climate factors include air temperature, humidity, sunlight intensity, and wind speed. This research aims to determine the impact of rainfall and climate conditions on agricultural lands. The study utilizes descriptive analysis of climate data and its influence on agricultural lands. The research findings reveal that the average monthly rainfall in Kediri district, West Lombok Regency, is approximately 222.75 mm. The average temperature is 26.7 degrees Celsius, with an average humidity of 84.5%, average sunlight intensity of 65.9%, and an average wind speed of 3.1 knots. These rainfall and climate conditions can affect water availability, soil microbe growth, plant photosynthesis processes, and plant pollination processes in agricultural lands.